Comparing the Financial Literacy of Public School, Christian School, and Homeschooled Students. Issue 1 (2nd January 2016) - Wright, Tricia
ABSTRACT: The 2008 recession underscored public concern that financial illiteracy has costs that are not limited to the individual who makes poor financial decisions. Considering that college students with limited financial experience are making legally binding decisions, this study explored the personal finance literacy and behavior of Christian college students. The research involved administering an objective item financial literacy and behavior survey. Findings showed a significant positive correlation between financial literacy and behavior. Furthermore, there was no significant difference among Christian college students based on their secondary education experience—Christian, public, or home school. This finding implies that students enter college with similar financial literacy levels, and senior students with inadequate financial literacy demonstrate poor personal financial behavior.